Trade Costs in the Developing World : 1995 - 2010 - Arvis, Jean-François; Duval, Yann; Shepherd, Ben; Utoktham, Chorthip (World Bank, Washington, DC, 2013)
The authors use newly collected data on trade and production in 178 countries to infer estimates of trade costs in agriculture and manufactured goods for the 1995-2010 period. The data show that trade costs are strongly declining in per capita income. Moreover, the rate of change of trade costs is largely unfavorable to the developing world: trade costs are falling noticeably faster in developed countries than in developing ones, which serves to increase the relative isolation of the latter. In particular, Sub-Saharan African countries and low-income countries remain subject to very high levels of trade costs. In terms of policy implications, the analysis finds that maritime transport connectivity and logistics performance are very important determinants of bilateral trade costs: in some specifications, their combined effect is comparable to that of geographical distance. Traditional and non-traditional trade policies more generally, including market entry barriers and regional integration agreements, play a significant role in shaping the trade costs landscape.